2012
DOI: 10.1039/c2ra20578e
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a renewable amide, 3-acetamido-5-acetylfuran, via direct conversion of N-acetyl-d-glucosamine

Abstract: An effective method for transforming an amino-sugar into an N-substituted furan in an ionic liquid is reported. B(OH) 3 significantly improves the yield (60%, 3 min MW heating).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 18 publications
0
96
0
1
Order By: Relevance
“…78 In the work of Franich et al, a mechanism of dehydration proceeding via an anhydrosugar intermediate was proposed. In our research, 80 we have proposed a mechanism that proceeds through an open-chain aldose form of the hexose in line with mechanisms proposed for dehydrations of fructose. In 1998, Chen et al pyrolyzed NAG at 200°C for 30 min.…”
Section: 74mentioning
confidence: 69%
See 1 more Smart Citation
“…78 In the work of Franich et al, a mechanism of dehydration proceeding via an anhydrosugar intermediate was proposed. In our research, 80 we have proposed a mechanism that proceeds through an open-chain aldose form of the hexose in line with mechanisms proposed for dehydrations of fructose. In 1998, Chen et al pyrolyzed NAG at 200°C for 30 min.…”
Section: 74mentioning
confidence: 69%
“…83 However, when reactions were performed in dipolar aprotic solvents or in some imidazolium ionic liquids in the presence of chloride ions and boric acid, 3A5AF was obtained. 80,84 In both studies, under optimized conditions, 60% yield of 3A5AF could be obtained, which is approximately 30 times greater than the yields via pyrolysis. In reactions performed in organic solvents, the highest yields were obtained in DMA, DMF and DMSO, however, we also noted that significant conversion levels could be achieved in the 'greener' solvents ethyl lactate and PEG.…”
Section: 74mentioning
confidence: 88%
“…60 % of 3A5AF has been obtained by using boric acid as the promoter. Microwave-irradiation was adopted as an efficient heating method and the dehydration reaction was carried out in both ionic liquids (ILs) and organic solvents at 180 and 220°C respectively [34,35]. The exceptional promotional effect of boric acid in NAG conversion has been ascribed to the possible formation of borate-hexose complex, which shifts the hexose-aldose equilibrium to the generation of linear form aldose.…”
Section: Conversion Of Chitin Monomermentioning
confidence: 99%
“…It could be a precursor of polyamide proximicines [149] that are isolated from Verrucosispora, a marine actinomycete. The product formation could be accelerated by the addition of different additives -the highest yield of 60% was achieved when boric-acid was used in 10 mol% concentration in [BMIM][Cl] at 180 • C. The kinetic study of the reaction revealed that the activation energy was 82.8 kJ/mol [150]. The yield can slightly be increased by the addition of NaCl and the application of higher temperature (220 • C) [151].…”
Section: Fundamental Reactions Involving Watermentioning
confidence: 86%